The impact of American and Russian Cosmism on the representation of space exploration in 20th century American and Soviet space art - Boczkowska, Kornelia (Wydawnictwo Naukowe UAM, 2016)
The aim of this dissertation is to explore and compare the impact of Russian and American Cosmism on the representation of space exploration in selected 20th century American and Soviet space art works in the context of both nations’ culture and literature of the period. The source material are 200 works of American (100) and Soviet (100) space art (1944-1991) which become subject to visual content analysis whose purpose is to examine the relation between the chief assumptions of Russian and American Cosmism and the image of space exploration constructed by American and Soviet artists. The research results obtained from the study have suggested that while the investigated representation of space exploration in the Soviet works can reflect approximately 70% of primary assumptions of Russian Cosmism, its depiction in the U.S. images seems to conceptualize approximately 80% of American Cosmism’s chief tenets.

Celem monografii jest analiza wpływu idei rosyjskiego i amerykańskiego kosmizmu na obraz podboju kosmosu w wybranych dziełach XX-wiecznej amerykańskiej i radzieckiej sztuki kosmicznej w ich kontekście kulturowym i literackim. Materiałem źródłowym jest 200 dzieł amerykańskiej i radzieckiej sztuki kosmicznej (1944-1991), poddanych analizie treści wizualnej mającej na celu zbadanie relacji między głównymi założeniami rosyjskiego i amerykańskiego kosmizmu a wizerunkiem podboju kosmosu skonstruowanym przez amerykańskich i radzieckich artystów. Badanie wykazało, że w reprezentacji eksploracji kosmosu w amerykańskich dziełach można zaobserwować wpływ około 80% głównych założeń amerykańskiego kosmizmu, takich jak mit amerykańskiego pogranicza, ideologia Boskiego Przeznaczenia, Efekt Nadwidzenia, nostalgia za programem Apollo, paradygmat von Brauna lub projekt SETI. Tymczasem obraz podboju kosmosu w radzieckiej sztuce może odzwierciedlać około 70% podstawowych założeń rosyjskiego kosmizmu, w szczególności elementy koncepcji „zwykłego czynu” Fiodorowa, rosyjskiej duszy Bierdiajewa, kosmicznego entuzjazmu, społecznego techno-utopianizmu czy też „szturmu nieba”.
Keywords: Russian Cosmism; American Cosmism; American space art; Soviet space art; Space exploration